2020
DOI: 10.1039/c9ra09801a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in printable thermoelectric devices: materials, printing techniques, and applications

Abstract: Additive printing as a low-cost and efficient fabrication technique for thermoelectric device is reviewed targeting the application of energy harvesting from human body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 108 publications
(110 reference statements)
0
32
0
Order By: Relevance
“…[698,700] For example, inorganic nanomaterials were added into polymers to achieve high thermoelectric performance. [707,708] The main design challenge in a TEG is to maximize the temperature difference across the hot-cold junctions. There are mainly two categories of TEGs, planar TEGs, where the junctions are on the same plane to the substrate, and through-plane TEGs, where the junctions are normal to the substrate.…”
Section: Energy-harvesting Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…[698,700] For example, inorganic nanomaterials were added into polymers to achieve high thermoelectric performance. [707,708] The main design challenge in a TEG is to maximize the temperature difference across the hot-cold junctions. There are mainly two categories of TEGs, planar TEGs, where the junctions are on the same plane to the substrate, and through-plane TEGs, where the junctions are normal to the substrate.…”
Section: Energy-harvesting Devicesmentioning
confidence: 99%
“…[12,701] To create a temperature difference across planar devices that are suitable for harvesting the thermal energy from the human body device configuration such as corrugation, origami, z-scheme folding, and vertical staking have been developed. [695,707] Printing methods such as inkjet printing, aerosol jet printing, DIW, and spray coating have been used to fabricate TEGs. [706,707,709,710] Madan et al demonstrated the DIW of mechanically alloyed (MA) n-type Bi 2 Te 3 composite to fabricate TEGs in a cost-effective and scalable way.…”
Section: Energy-harvesting Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…2022, 34, 2108183 where the solute within the deposited ink flows to the outside of the deposited droplet via capillary effects as it dries, causing the inside of the droplet to be thinner, this can cause uneven characteristics within the ink. [28] Films and devices produced via inkjet printing are also very thin (≈0.4-1.6 µm). [29] Dispenser printing (Figure 3d) is a simple process that consists of a syringe that deposits ink onto a substrate through a needle.…”
Section: Introductionmentioning
confidence: 99%
“…22 The ltration efficiency is improved with the help of increasing surface area of the porous architecture. 23 The porous lters are fabricated by gas foaming, solvent casting/particulate leaching, freeze-drying, and 3D printing [24][25][26][27][28][29] techniques. Among these, 3D printing is the competitive technique due to its numerous advantages, such as its capability to fabricate complex structures, agility to print a wide spectrum of compatible materials, sustainability, and scalability.…”
Section: Introductionmentioning
confidence: 99%